2021
DOI: 10.1002/anie.202014540
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Structural Diversity of Protein Building Blocks with Noncanonical Amino Acids Biosynthesized from Aromatic Thiols

Abstract: Incorporation of structurally novel noncanonical amino acids (ncAAs) into proteins is valuable for both scientific and biomedical applications.Toexpand the structural diversity of available ncAAs and to reduce the burden of chemically synthesizing them, we have developed ageneral and simple biosynthetic method for genetically encoding novel ncAAs into recombinant proteins by feeding cells with economical commercially available or synthetically accessible aromatic thiols.W ed emonstrate that nearly 50 ncAAs wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…5 , PDB ID “ 6DN0 ”). The protein was produced and purified from the periplasmic space 41 , 42 , in E. coli BL21 (DE3) co-transformed with pULTRA-pTAFRS and pET22b-HER2-scFv-S9/K42/V15TAG plasmids. A HER2-scFv-K42 pTAF mutant, which had a high expression yield (30 mg/L), was chosen for further characterization; and the mutant and wild-type proteins were confirmed by SDS–PAGE and high-resolution mass spectrometry (Supplementary Figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 , PDB ID “ 6DN0 ”). The protein was produced and purified from the periplasmic space 41 , 42 , in E. coli BL21 (DE3) co-transformed with pULTRA-pTAFRS and pET22b-HER2-scFv-S9/K42/V15TAG plasmids. A HER2-scFv-K42 pTAF mutant, which had a high expression yield (30 mg/L), was chosen for further characterization; and the mutant and wild-type proteins were confirmed by SDS–PAGE and high-resolution mass spectrometry (Supplementary Figs.…”
Section: Resultsmentioning
confidence: 99%
“…It would have the potential for enhanced tumor penetration and better in vivo pharmacokinetics. J591 Fab containing a A121 pTAF mutation, where the alanine at 121 position was mutated to ncAA pTAF by site-directed mutagenesis of alanine codon to an amber codon, was purified from the periplasmic space in E.coli BL21(DE3) along with the wild-type protein 41 . A121 site was chosen on the basis of its surface accessibility, high expression yield and high conjugation efficiency 10 .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the distribution of over-expressed OmpC on E. coli cells of interest could be captured in vitro in 3D space by implementing a designated illumination, which offers a protocol for exploring their dynamic processes in living systems. The successful incorporation of DBTDA also provides a chemical transducer for photochemical energy conversion 23 on key loci of proteins, which could be further exploited in the patterning of proteins in biomaterials 24 and the enrichment of protein molecular machines 25 for synthetic biology, 26 as well as protein photo-pharmaceuticals for precision medicine. 27 The xolographic fabrication of artificial protein copolymers 28 can also be envisioned because DASyd and DBTDA can be photo-activated separately.…”
Section: Introductionmentioning
confidence: 99%
“…Work by Di Salvo and collaborators showed how the hijacking of methionine biosynthesis of E. coli, via the introduction of acetylated homoserine (two genes from a Corynebacterium were actually used for direct sulfhydration), can be used for in situ production of different ncAAs [22][23][24]. Phosphothreonine, which has an impenetrable cell membrane, could be biosynthesized and genetically encoded into protein [25], and, recently, it was shown that the cysteine biosynthetic enzymes could be hijacked to introduce multiple homophenylalanine derivatives [26].…”
Section: Introductionmentioning
confidence: 99%